A Middleware for Self-Organising Distributed Ambient Assisted Living Applications - Schaefer, Jan (Electronic Communications of the EASST, 2010)
This paper presents a middleware approach for self-organising distributed applications in the area of Ambient Assisted Living (AAL) as part of a home service platform. The middleware uses real time data processing techniques to identify complex events based on sensor input and service logs. This low-level and high-level information represents the platform’s context model, which forms the basis for self-organisation properties: Controllers use context information to manage running services while adhering to strategies defined by users or inferred by the system itself.